KERUKUNAN ANTAR UMAT BERAGAMA DALAM PANDANGAN AGAMA BUDDHA - Dharmaji Chowmas (Lembaga penelitian dan pengabdian kepada masyrakat, 2009)
Religious harmony is the condition for all religious groups could live together peacefully without prejudice to the rights and freedom of each to adopt and carry out their religious obligations. Harmony is religious does not mean that one does not feel the need or help with diversity issues involving other parties, because the collective wills of tolerance, that really possible if mutual understanding. Harmony will be achieved if every religious group has agreed in principle the difference. Agreed in the difference means people will accept and respect others with all the aspirations, beliefs, habits and patterns of life, accept and respect others with the freedom to adopt their own religious beliefs. maintaining religious harmony does not mean maintaining the status quo so that impede the progress of each religion. Harmony that must be seen in the context of the dynamic development of society, who face various challenges and problems.